PERTANGGUNGJAWABAN PIDANA PENYALAHGUNAAN KARTU KREDIT OLEH PENGGUNA KARTU KREDIT - Desy Kartika Caronina Sitepu; Syafruddin Kalo; Madiasa Ablisar; Utary Maharani Barus (USU LAW JOURNAL, 2015)
ABSTRACT The presence of banks in Indonesia have a very important role in national development, especially economic development. The form of the criminalization lead to banking crime is a form of criminal offenses in the field of banking. Criminal acts which appear in the use of the credit card fraud, theft, and forgery. Type of research is that normative legal research using appropriate legal norms or criminal liability relating to the offense of credit card abuse. To see criminal responsibility in the crime of credit card misuse by the user either forgery, theft and fraud to be seen of the elements of accountability that is the criminal responsible, an error and there is no excuse. In the consideration of the judge in ruling on credit card users who commit criminal acts of credit card misuse at three District Court No. 8 / Pid.B/ 2011/ PN.Ung, District Court Decision No. 2156 /Pid.B /2013/PN.Sby, and Court Decisions No. 119 / Pid.B/ 2013/ PN.Jkt. Sel the judges consider that all three cases have met the elements of the crime of misuse of credit cards be it in the form of fraud, theft, and forgery against credit card charges made in accordance with the perpetrators. Keywords : Crimal Liability, misuse of credit cards, credit card users